Integrated respiratory chemoreflex‐mediated regulation of cerebral blood flow in hypoxia: Implications for oxygen delivery and acute mountain sickness. Issue 9 (16th August 2021) - Ogoh, Shigehiko; Washio, Takuro; Stacey, Benjamin S.; Tsukamoto, Hayato; Iannetelli, Angelo; Owens, Thomas S.; Calverley, Thomas A.; Fall, Lewis; Marley, Christopher J.; Saito, Shotaro; Watanabe, Hironori; Hashimoto, Takeshi; et al.
Abstract : New Findings: What is the central question of this study? To what extent do hypoxia‐induced changes in the peripheral and central respiratory chemoreflex modulate anterior and posterior cerebral oxygen delivery, with corresponding implications for susceptibility to acute mountain sickness? What is the main finding and its importance? We provide evidence for site‐specific regulation of cerebral blood flow in hypoxia that preserves oxygen delivery in the posterior but not the anterior cerebral circulation, with minimal contribution from the central respiratory chemoreflex. External carotid artery vasodilatation might prove to be an alternative haemodynamic risk factor that predisposes to acute mountain sickness. Abstract: The aim of the present study was to determine the extent to which hypoxia‐induced changes in the peripheral and central respiratory chemoreflex modulate anterior and posterior cerebral blood flow (CBF) and oxygen delivery (CDO2 ), with corresponding implications for the pathophysiology of the neurological syndrome, acute mountain sickness (AMS). Eight healthy men were randomly assigned single blind to 7 h of passive exposure to both normoxia (21% O2 ) and hypoxia (12% O2 ). The peripheral and central respiratory chemoreflex, internal carotid artery, external carotid artery (ECA) and vertebral artery blood flow (duplex ultrasound) and AMS scores (questionnaires) were measured throughout. A reduction in internal carotid artery CDO2 was observed during hypoxia despite a compensatory elevation in perfusion. In contrast, vertebral artery and ECA CDO2 were preserved, and the former was attributable to a more marked increase in perfusion. Hypoxia was associated with progressive activation of the peripheral respiratory chemoreflex ( P < 0.001), whereas the central respiratory chemoreflex remained unchanged ( P > 0.05). Symptom severity in participants who developed clinical AMS was positively related to ECA blood flow (Lake Louise score, r = 0.546–0.709, P = 0.004–0.043; Environmental Symptoms Questionnaires‐Cerebral symptoms score, r = 0.587–0.771, P = 0.001–0.027, n = 4). Collectively, these findings highlight the site‐specific regulation of CBF in hypoxia that maintains CDO2 selectively in the posterior but not the anterior cerebral circulation, with minimal contribution from the central respiratory chemoreflex. Furthermore, ECA vasodilatation might represent a hitherto unexplored haemodynamic risk factor implicated in the pathophysiology of AMS. Abstract :